Notes on Gunnera (Gunneraceae) in Brazil and Uruguay - Hassemer, Gustavo (Phytotaxa, 2019)
Nomenclatural notes on the species of Gunnera that occur in Brazil and Uruguay are presented. More specifically, I designate a lectotype for the name G. herteri, the only species in Gunnera subg. Ostenigunnera, selected from among the collections of MVM, where Cornelius Osten’s personal herbarium is conserved. I also designate a lectotype for the name G. brasiliensis, a legitimate heterotypic synonym of G. manicata, which has been considered by some authors as an illegitimate, superfluous name. Furthermore, I provide an identification key to Gunnera in Brazil and Uruguay.